Analysis of discarding policies in high-speed networks. - Lapid, Y. (IEEE Journal on selected areas in communications)
Networked applications generate messages that are segmented into smaller, fixed or variable size packets, before they are sent through the network. In high-speed networks, acknowledging individual packets is impractical; so when congestion builds up and packets have to be dropped, entire messages are lost. For a message to be useful, all packets comprising it must arrive successfully at the destination. The problem is therefore which packets to discard so that as many complete messages are delivered, and so that congestion is alleviated or avoided altogether. Selective discarding policies, as a means for congestion avoidance, are studied and compared to nondiscarding policies. The partial message discard policy discards packets of tails of corrupted messages. An improvement to this policy is the early message discard that drops entire messages and not just message tails. A common performance measure of network elements is the effective throughput which measures the utilization of the network links but which ignores the application altogether. We adopt a new performance measure-goodput-which reflects the utilization of the network from the application's point of view and thus better describes network behavior. We develop and analyze a model for systems which employ discarding policies. The analysis shows a remarkable performance improvement when any message-based discarding policy is applied, and that the early message discard policy performs better than the others, especially under high load. We compute the optimal parameter setting for maximum goodput at different input loads, and investigate the performance sensitivity to these parameters